2021
DOI: 10.1002/cbin.11634
|View full text |Cite
|
Sign up to set email alerts
|

BVES‐AS1 inhibits the malignant behaviors of colon adenocarcinoma cells via regulating BVES

Abstract: The underexpression of the long noncoding RNA blood vessel epicardial substance antisense RNA 1 (BVES‐AS1) has been shown in colon adenocarcinoma (COAD) patients. However, its role in COAD remains to be explored. This study aimed to investigate the function and potential mechanism of BVES‐AS1 in COAD. Colony formation, Cell Counting Kit‐8, JC‐1 mitochondrial membrane potential assay, wound healing, transwell, and western blot analyses were used to measure cell proliferation, apoptosis, migration, invasion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
1
2
0
Order By: Relevance
“… 24 It has also been reported that BVES-AS1 lncRNA inhibited colorectal adenocarcinoma progression via interacting with hsa-miR-522-3p. 25 In our study, hsa-miR-522-3p was induced 12.41-fold after treating with ST in H508 cells. On the contrary, there was no significant change in hsa-miR-522-3p expression after treating with ST in SNU-C4 cells.…”
Section: Discussionsupporting
confidence: 47%
“… 24 It has also been reported that BVES-AS1 lncRNA inhibited colorectal adenocarcinoma progression via interacting with hsa-miR-522-3p. 25 In our study, hsa-miR-522-3p was induced 12.41-fold after treating with ST in H508 cells. On the contrary, there was no significant change in hsa-miR-522-3p expression after treating with ST in SNU-C4 cells.…”
Section: Discussionsupporting
confidence: 47%
“…Previous work proved that lncRNA BVES-AS1 can operate as a tumor suppressor in CRC by repressing colon adenocarcinoma cell growth, motility, and metastasis through the miR-522-3p/BVES cascade [ 34 ]. Our current study suggests the tumor-promoting activity of BVES-AS1-201-50aa in CRC, indicating that BVES-AS1 and its peptide BVES-AS1-201-50aa have opposite effects in regulating colorectal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GI system, in colorectal cancer cell cultures, the interaction of long noncoding RNA blood vessel epicardial substance (BVES) antisense RNA 1 with miR-522-3p and TAF15 has been demonstrated to regulate BVES expression, which might offer a perspective for colorectal cancer treatment, but further study is needed[ 38 ]. In an elegant study, Tang et al [ 15 ] revealed significant upregulation of TAF15 in gastric cancer (GC) tumor tissues and cell lines.…”
Section: Taf15 In Gi Cancersmentioning
confidence: 99%